Phytoremediation of Linear Alkylbenzene Sulfonate (LAS) Detergent Using Azolla microphylla and Ludwigia adscendens - Ifa Ulya Fitriyani; Fida Rachmadiarti (Jurnal Biologi Tropis, 2026)
The increasing use of detergents has the potential to cause water pollution due to their surfactant content, particularly Linear Alkylbenzene Sulfonate (LAS), which is toxic to aquatic organisms and poses a risk to human health. One approach to mitigating LAS pollution is phytoremediation. Although phytoremediation has been widely practiced, studies comparing the effectiveness of two plant species remain limited. This study aims to determine the effects of plant species, LAS concentration, and their interaction on the reduction of LAS levels in water, chlorophyll levels in leaves, and plant fresh biomass. This study is an experimental study using a Randomized Block Design (RBD) with two treatment factors: plant species (Azolla microphylla and Ludwigia adscendens) and LAS concentration (0 ppm, 10 ppm, and 20 ppm). The observed parameters included LAS concentration in water, leaf chlorophyll content, and plant fresh biomass, which were analyzed using two-way ANOVA and Duncan’s test, and environmental physicochemical parameters were analyzed using quantitative descriptive analysis and compared with applicable quality standards. The results showed that plant species, LAS concentration, and their interaction significantly affected LAS concentration in water, leaf chlorophyll content, and plant fresh biomass. The highest reduction in LAS occurred in the Ludwigia adscendens treatment (10 ppm) at 99.200%, while the lowest was in the Azolla microphylla treatment (20 ppm) at 96.983%. The results of the study prove that Azolla microphylla and Ludwigia adscendens have the potential to be used as phytoremediation agents for LAS contamination.